Analysis of single and multi-wall carbon nanotubes (SWCNT/MWCNT) in the flow of Maxwell nanofluid with the impact of magnetic dipole - Kumar, Varun; Madhukesh, J.K.; Jyothi, A.M.; Prasannakumara, B.C.; Ijaz Khan, M.; Chu, Yu-Ming (Computational and theoretical chemistry, 2021)
Diagrammatic illustration of the flow problem. [Display omitted] •Here flow of Maxwell nanofluid towards a stretched surface is examined.•Both single and multi-wall carbon nanotubes are considered.•Magnetic dipole is accounted.•Numerically results are obtained through using Runge-Kutta Fehlberg 45 order (RFF 45). The study of non-Newtonian fluids flow over diverse geometries with significant physical implications has numerous applications in the manufacturing and engineering field. On the other hand, carbon nanotubes (CNT) have wide-ranging applications in nanotechnology, energy storage, industry, chemical sensors, conductive plastics, optics, and structural composite materials. Hence, the flow of Maxwell nanoliquid embedded with SWCNT/MWCNT over a stretching sheet with the consideration of thermal radiation and magnetic dipole is examined. The partial differential equations (PDEs) specifying the flow of liquid are transformed into ordinary differential equations (ODEs) with the assistance of suitable similarity transformations. The reduced ODEs are numerically solved by using Runge-Kutta Fehlberg 45 order (RFF 45) method with the aid of shooting scheme. Major result outcome unveils that, fluid velocity decreases with an upsurge of ferromagnetic interaction parameter thermal distribution enhances rapidly for heightening of Biot number and thermal radiation parameter. Rate of heat transfer growths with higher values of Biot number and thermal radiation parameter. Surface drag force enhances with heightens values of solid volume fraction but decreases for viscous dissipation parameter.